Luxembourg : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2002)
The 2002 Article IV Consultation highlights that the financial sector of Luxembourg has continued to expand, with asset and liquidity management taking over from private banking as the main source of strong growth of the sector. Nonetheless, activity weakened in 2001. Structural reforms are proceeding. Progress has been made in removing legal obstacles to part time employment, introducing more flexible working time arrangements and work-week averaging, and expanding child care facilities. The authorities have adopted the legal and regulatory framework needed for the launch of an electronic commerce sector.